ANALISIS STRATEGI PENGENDALIAN KSPPS ARRAHMAH DALAM MENEKAN TINGKAT NPF DI MASA PANDEMI COVID-19 - Rani Riyantari (2021)
The outbreak of the Covid-19 virus and the implementation of large-scale social restrictions implemented in Indonesia have caused many company performances to decline, one of which is savings and loan cooperatives and sharia financing. The impact faced by cooperatives is an increase in the value of non-performing financing due to the Covid-19 pandemic. Therefore, this study aims to analyze the control strategy carried out by cooperatives to reduce the level of non-performing financing by referring to Government Regulation no. 7 and MUI Fatwa No. 47, 48, and 49. This research uses descriptive qualitative with case study research type. Data collection techniques used are structured interviews, passive participant observation, and documentation. The researcher used triangulation technique to test the validity of the data, and the researcher carried out data reduction, data presentation, and conclusion drawing/verification for data analysis. The results of this study indicate that the increase in the level of non-performing financing is caused by internal and external factors, which come from cooperatives and cooperative members, respectively. Researchers found that there are control strategies in accordance with Government Regulations and MUI Fatwas, including consolidation, optimization of billing and monitoring systems, revitalizing processes through restructuring and rescheduling, collacteral, and write-offs. Keywords: control strategies, Covid-19, KSPPS, NPF